Attitudes and psychotropic preferences of primary care providers in the management of mental disorders: a web-based survey - Örüm, Dilek (Frontiers in Medicine, 2024)
Background: Many variables may affect the approaches of primary care providers (PCPs) to mental disorders. This study was aimed at reaching PCPs actively practicing in Turkey through a web-based survey and determining their practices and attitudes regarding mental disorders. Methods: This was a web-based, quantitative, cross-sectional, primary care approach-based observational survey. Results: Data from 454 PCPs (213 male, 241 female; 321 general practitioners, 133 family medicine specialists) were examined. In-service training in psychiatry (p<0.001), using classification criteria when evaluating mental disorders (p<0.001), and experience in diagnosing mental disorders (p=0.003) were more prevalent among family medicine specialists than general practitioners. Regardless of specialization status, PCPs reported the most difficulty diagnosing bipolar disorder (62.33%) and following-up alcohol/drug use disorder (52.20%). Significant differences in the use of psychotropic medications were observed between general practitioners and family medicine specialists. While the rate of direct referral to psychiatry without intervening in certain situations was higher among general practitioners, variety of psychotropic medication use were also more evident among them. Misinformation that antidepressants cause forgetfulness, numbness, suicide, and addiction was prevalent among all PCPs. Those who had in-service training in psychiatry had significantly more experience in using classification criteria, diagnosing and starting treatment for mental disorders, using psychotropic medications, and encountering suicide-related situations (p<0.05). Binary logistic regression analysis demonstrated that psychiatry in-service training experience can improve the use of classification criteria, suicide detection, antidepressant choice in anxiety, and understanding the addictive nature of antidepressants (Sensitivity=88.6%; Specificity=98.3%; Beginning block -2 Log likelihood 628.946, overall p value<0.001; Block one -2 Log likelihood 141.054a, Cox & Snell R2=0.659, Nagelkerke R2=0.878; Hosmer and Lemeshow Test p=0.938). Conclusions: This study makes significant contributions to the literature by discussing the subject in detail and comparing general practitioners and family medicine specialists. Regardless of their specialty status, PCPs’ knowledge about mental disorders needs to be improved. In-service psychiatry training is one of the tools that can be used for this purpose.